Assessing the trophic ecology of three sympatric squid in the marine ecosystem off the Patagonian Shelf by combining stomach content and stable isotopic analyses. Issue 4 (20th April 2016) - Rosas-Luis, Rigoberto; Navarro, Joan; Sánchez, Pilar; Del Río, José L.
ABSTRACT: Squid species are important components of the Southern Atlantic Ocean ecosystems, as they prey on a wide range of crustaceans, fish and cephalopods. As a result of this trophic interaction and their high abundance, they are considered reliable indicators of energy transfer and biomass in the food web. We identified Illex argentinus, Doryteuthis gahi and Onykia ingens as the most important squid species interacting on the Patagonian shelf, and used isotope analysis and stomach content identification to assess the feeding ecology and interaction of these squids in the ecosystem. Our results describe trophic interactions by direct predation of O. ingens and I. argentinus on D. gahi, and a trophic overlap of the three squid, and indicate a higher trophic level and differences in the foraging areas for mature and maturing D. gahi inferred through δ 15 N and δ 13 C concentrations. These differences were related to the segregation and different habitat of large mature D. gahi and suggest a food enrichment of C and N based on feeding sources other than those used by small maturing D. gahi and I. argentinus and O. ingens .